2016
DOI: 10.1074/mcp.m115.055541
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant-induced Human Monocyte Secretome Profiles Reveal Adjuvant- and Age-specific Protein Signatures

Abstract: Adjuvants boost vaccine responses, enhancing protective immunity against infections that are most common among the very young. Many adjuvants activate innate immunity, some via Toll-Like Receptors (TLRs), whose activities varies with age. Accordingly, characterization of age-specific adjuvant-induced immune responses may inform rational adjuvant design targeting vulnerable populations. In this study, we employed proteomics to characterize the adjuvant-induced changes of secretomes from human newborn and adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 67 publications
1
20
0
Order By: Relevance
“…Human newborn and adult monocytes exhibit distinct responses to adjuvants and licensed adjuvanted vaccines in vitro that demonstrate age- and adjuvant-specific correlations to adjuvanted vaccine-induced responses in vivo 99 . Moreover, TLR agonist administration to newborn mice enhances their subsequent cytokine and phagocytic responses to polymicrobial sepsis 100 , and early inflammatory/innate immune-activating events in humans are associated with reduced risk of late-onset sepsis 82, 83 .…”
Section: Perspectives For Vaccinologymentioning
confidence: 96%
“…Human newborn and adult monocytes exhibit distinct responses to adjuvants and licensed adjuvanted vaccines in vitro that demonstrate age- and adjuvant-specific correlations to adjuvanted vaccine-induced responses in vivo 99 . Moreover, TLR agonist administration to newborn mice enhances their subsequent cytokine and phagocytic responses to polymicrobial sepsis 100 , and early inflammatory/innate immune-activating events in humans are associated with reduced risk of late-onset sepsis 82, 83 .…”
Section: Perspectives For Vaccinologymentioning
confidence: 96%
“…We have previously demonstrated that several of these licensed vaccines, such as the EasyFive (DTwP-HepB-Hib), induce distinct reactogenicity biomarker profiles in vitro (31, 32). When tested at equivalent v/v treatment concentrations, Δ lpxLI nOMV conversely induced a lower cytokine response for most innate cytokines (Figures 4A,B) and chemokines (Figure S7 in Supplementary Material) tested, grouping closer to pediatric vaccines such as PCV13 and HBV, than the more inflammatory (Alum + TLR agonist)-containing pediatric vaccines (i.e., PedvaxHIB and EasyFive).…”
Section: Resultsmentioning
confidence: 99%
“…Next, immature newborn (Figure 5A) and adult DCs (Figure 5B) were assessed for vaccine-induced production of PGE 2 , a molecule whose in vitro production has been correlated with reactogenicity in vivo (3133). Of note, newborn DCs demonstrated significantly reduced Δ lpxLI nOMV-mediated PGE 2 responses as compared to both Bexsero ( p  < 0.01) and WT dOMV (with Alum) ( p  < 0.05) (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it altered the phenotype of the recruited cells, including increased activation status, phagocytosis and NET formation, with a significant reduction in the bacterial colonization. Recently, the global proteomic response of human neonatal monocytes to alum demonstrated the activation of phagocytosis-related signalling (caveolarmediated endocytosis, MSP-RON) when monocytes were stimulated with alum in vitro [34]. Professional phagocytic cells such as macrophages are able to sense alum crystals in vitro via the activation of the NLRP3 inflammasome [35].…”
Section: Discussionmentioning
confidence: 99%